Factors influencing student retention university students: an analysis of institutional reputation, social responsibility and loyalty - Albornoz-Toyohama, Roger Hiroshi; Mendigure-Hachircana, Ruth; Haro-Casildo, Sady; Abanto-Ramírez, Carlos D. (Frontiers in Education, 2025)
IntroductionThis study investigates the impact of institutional reputation (IR), social responsibility (SR) and student loyalty (LY) on student retention (RT) in university students.MethodsUsing a quantitative, non-experimental, cross-sectional design, 409 students of private universities, both domestic and foreign, were surveyed.ResultsAnalysis using Partial Least Square Structural Equation Modeling (PLS-SEM) revealed that SR positively influences LY (β = 0.218, p < 0.001) and RT (β = 0.123, p = 0.006). LY showed a strong impact on RT (β = 0.765, p < 0.001), whereas IR significantly influenced LY (β = 0.556, p < 0.001). Contrary to expectations, no direct relationship was found between institutional reputation and retention. In addition, it was shown that SR had a positive effect on IR (β = 0.531, p < 0.001).ConclusionBased on the results obtained, it is concluded that SR positively predicts LY, RT and IR, Ly positively predicts RT and IR LY, with significant implications for university management and research at this educational level.